SUITABILITY TEST OF WAGNER SCALE AND BATES-JENSEN IN EVALUATING THE HEALING GRADE OF DIABETIC ULCER PATIENTS - Asbaningsih, Febrianti; Gayatri, Dewi (ETN Centre Indonesia, 2016)
Background : Diabetic ulcer is one of the complications of diabetes mellitus which require appropriate wound evaluation instruments to determine the proper treatment in order to avoid more severe condition. The study objective was to identify the relationship between the Wagner scale wound assessment instruments and Bates- Jensen Wound Assessment Tool (BWAT) in patients with diabetic ulcers. Methods: The study design was descriptive cross sectional study. The samples of this study were 43 patients with diabetic ulcer. The instrument used was the Wagner scale to measure the severity of the diabetic ulcers patient's wound and the BWAT used to measure the severity of the patient's decubitus ulcer wounds. Results: The result of statistical tests showed that there was a strong correlation between the Wagner scale instrument and the BWAT in assessing diabetic ulcer wounds (r = 0.789, p = 0.0005). Conclusions: The results of the study showed that the BWAT can be used to evaluate diabetic ulcer wounds. Therefore it could be recommended to use BWAT for evaluating wound healing in patients with diabetic ulcer is clinical setting. Keywords: Bates-Jensen Wound Assessment Tool, diabetic ulcer, Wagner scale